An Interpretation of the Architecture of the Mohammed V Mausoleum in Avant-Garde Fashion Through Fabric Manipulation Techniques - Adinka Putril Laksmi; Ratna Suhartini; Indarti Indarti (Universitas Negeri Surabaya, 2026)
This study interprets the architecture of the Mohammed V Mausoleum into avant-garde fashion by applying a combination of fabric manipulation techniques, namely applique, cording, and tucking. The research employed a practice-based design research approach using the Double Diamond model, consisting of Discover, Define, Develop, and Deliver stages. Data were collected through visual observation, design documentation, and expert judgment involving three fashion design experts using a Guttman scale instrument. The data were analyzed using descriptive quantitative analysis through percentage calculations and supported by interpretative visual analysis. The results show that architectural elements of the Mohammed V Mausoleum, particularly zellij geometric motifs, Moorish arches, wall ornaments, and monumental forms, were successfully translated into a three-piece avant-garde garment consisting of a hooded cape, bustier, and flared pants. Expert evaluation indicated that most indicators achieved 100%, while several aspects related to cording structure and final architectural embodiment achieved 66.7%. The applique and tucking techniques were effective in representing geometric ornamentation and arch structures, whereas the cording technique requires further refinement in line composition and motif proportion. This study demonstrates that Islamic architecture can serve as a relevant source of creative innovation in culturally inspired avant-garde fashion and fabric manipulation exploration.